'How well, not how much': The life and career of Maksymilian Rutkowski (1867–1947). (August 2018) - Pekacka-Falkowska, Katarzyna; Bogusz, Halina
Maksymilian Rutkowski (1867–1947) was a distinguished graduate of the Jagiellonian University and a pioneer in the early days of surgery in interwar Poland. He was a long-standing leader in both clinical and academic surgery. In addition, he played an important role in the founding of the School for Nurses and Healthcare Workers in Cracow supported by the Rockefeller Foundation. Among his best known surgical techniques, one may list the novel procedure of bladder exstrophy, new techniques of gastroenterostomy and plastic restoration of the oesophagus. Although Rutkowski's reputation as a medical figure is well established within Polish medical history, his achievements are hardly recognized by international scholars. Thus, in the absence of adequate historical information on this eminent surgeon, we have researched the main facts about his life and seminal contribution to Polish and international surgery.